DAMPAK BENCANA HIDROMETEOLOGI DI DESA KUALA CEURAPE, KECAMATAN JANGKA, KABUPATEN BIREUEN - Noratul Husna; Hariki Fitra; Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the impacts of hydrometeorological disasters on the physical environmental conditions, infrastructure and accessibility, as well as the social conditions of the community in Kuala Ceurape Village, Jangka District, Bireuen Regency. The study employed a qualitative approach with a descriptive research design. Data were collected through observations, in-depth interviews with 3 informants consisting of affected community members and village officials, and documentation. Data were analyzed through the stages of data reduction, data display, and conclusion drawing, with triangulation techniques used to ensure data validity. The findings revealed that hydrometeorological disasters caused environmental damage in the form of sedimentation, erosion, destruction of fishponds, agricultural land degradation, and deterioration of water quality. Infrastructure was damaged, including roads, bridges, drainage systems, irrigation networks, and electricity networks, which hindered community mobility. From the social perspective, the community experienced displacement, decreased income, health problems, and psychological trauma. Nevertheless, the community demonstrated strong social solidarity during the recovery process. This study is expected to serve as a reference for the government and the community in strengthening disaster mitigation and hydrometeorological disaster management efforts.